COMPETENCES OF HUMAN RESOURCE MANAGEMENT: EXPECTATIONS AND REALITY - Lobanova, Liudmila; Palekaitė, Airina; Radzevičiūtė, Justė (Ekonomika, 2009)
The competence of human resources specialists becomes more important nowadays due to the knowledge-based development of society and economics. It affects not only the quality of their own work, but also the efficiency, capacity and motivation of all the employees in an organization. The article deals with the composition of competences of human resources management, the profiles, responsibilities and functions of personnel managers. By means of theoretical studies and empirical research, the functions of personnel management and the related competences have been analysed with the aim to reveal employees’ expectations regarding personnel managers. The analysis has revealed the current situation in organizations. The results of the empiric research have shown which actions of the personnel management that refer to the competence of human resources management are most acceptable by the employees and how they are affected by these actions.p>